Effect of vildagliptin add-on treatment to metformin on plasma asymmetric dimethylarginine in type 2 diabetes mellitus patients - Cakirca M; Karatoprak C; Zorlu M; Kiskac M; Kanat M; Cikrikcioglu MA; Soysal P; Hursitoglu M; Camli AA; Erkoc R; Abdul-Ghani M (Dove Medical Press, 2014)
Mustafa Cakirca,1 Cumali Karatoprak,1 Mehmet Zorlu,1 Muharrem Kiskac,1 Mustafa Kanat,2 Mehmet Ali Cikrikcioglu,1 Pinar Soysal,3 Mehmet Hursitoglu,4 Ahmet Adil Camli,1 Reha Erkoc,1 Muhammad Abdul-Ghani5 1Internal Medicine Clinic, Faculty of Medicine, Bezmialem Vakif University, 2Department of Internal Medicine, Medical Faculty, Istanbul Medipol University, 3Department of Geriatric Medicine, Medical Faculty, Dokuz Eylül University, 4Department of Internal Medicine, Kanuni Sultan Suleyman Training and Research Hospital, Istanbul, Turkey; 5Division of Medicine – Diabetes, University of Texas Health Science Center at San Antonio, San Antonio, TX, USA Aims: A close association has been demonstrated between increased cardiovascular risk and high asymmetric dimethylarginine (ADMA) levels in type 2 diabetes mellitus (DM) patients. We planned to measure serum ADMA levels in type 2 DM patients using vildagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor. Materials and methods: A total of 68 type 2 DM patients who were on metformin were enrolled in the study. Based on the glycemic levels of patients, vildagliptin was added on to treatment in 33 patients. Patients were followed for 6 months. Serum ADMA, C-reactive protein, and fibrinogen levels were compared in groups of patients using metformin or metformin + vildagliptin, after 6 months. Results: Serum ADMA levels were found to be significantly lower in the group using vildagliptin compared to the group using metformin + vildagliptin (P<0.001). However, serum C-reactive protein and fibrinogen levels were statistically similar in the two study groups (P=0.34 and P=0.23, respectively). Conclusion: Metformin + vildagliptin treatment was observed to lower serum ADMA levels in type 2 DM patients. Our findings notwithstanding, large-scale prospective randomized controlled studies are warranted to conclude that vildagliptin provides cardiovascular protection along with diabetes regulation. Keywords: asymmetric dimethylarginine (ADMA), dipeptidyl peptidase-4 (DPP-4) inhibitor, vildagliptin, type 2 diabetes mellitus